The Applications of Cone-Beam Computed Tomography in Endodontics: A Review of Literature - Kiarudi, Amir Hosein; Eghbal, Mohammad Jafar; Safi, Yaser; Aghdasi, Mohammad Mehdi; Fazlyab, Mahta (Iranian Endodontic Journal, 2014)
By producing undistorted three-dimensional images of the area under examination, cone-beam computed tomography (CBCT) systems have met many of the limitations of conventional radiography. These systems produce images with small field of view at low radiation doses with adequate spatial resolution that are suitable for many applications in endodontics from diagnosis to treatment and follow-up. This review article comprehensively assembles all the data from literature regarding the potential applications of CBCT in endodontics.